Isaiah 1-39 - McKinion, Steven A. (Steven Alan); Oden, Thomas C. (Ancient Christian commentary on Scripture. Old Testament, 2014)
"For the early church fathers the prophecy of Isaiah was not a compendium of Jewish history or theology but an announcement of the coming Messiah fulfilled in the life and ministry of Jesus of Nazareth. As such, the prophet's words were a rich source of theological reflection concerning their Lord and a vital aid in their defense against the objections of the Jews that Jesus was the promised Messiah. The interpretation of Jesus' ministry in light of Isaiah's prophecy was not a theological innovation on their part but rather a following of the path blazed by the New Testament writers and Jesus himself." "Among passage-by-passage commentaries cited here are those by Eusebius of Caesarea, Jerome, Cyril of Alexandria and Theodoret of Cyr, as well as one attributed to Basil of Caesarea. John Chrysostom preached a series of homilies on Isaiah of which most of those extant concern the first eight chapters, though Chrysostom frequently cites Isaiah in numerous homilies on other books. Augustine of Hippo, Gregory the Great and Bede the Venerable frequently cite passages from Isaiah 1-39, as did many other fathers in defending the Christian faith from Jewish critics."--Jacket